Predicting Noninsulin Antidiabetic Drug Adherence Using a Theoretical Framework Based on the Theory of Planned Behavior in Adults With Type 2 Diabetes: A Prospective Study. Issue 15 (April 2016) - Zomahoun, Hervé Tchala Vignon; Moisan, Jocelyne; Lauzier, Sophie; Guillaumie, Laurence; Grégoire, Jean-Pierre; Guénette, Line
Abstract : Abstract: Understanding the process behind noninsulin antidiabetic drug (NIAD) nonadherence is necessary for designing effective interventions to resolve this problem. This study aimed to explore the ability of the theory of planned behavior (TPB), which is known as a good predictor of behaviors, to predict the future NIAD adherence in adults with type 2 diabetes. We conducted a prospective study of adults with type 2 diabetes. They completed a questionnaire on TPB variables and external variables. Linear regression was used to explore the TPB's ability to predict future NIAD adherence, which was prospectively measured as the proportion of days covered by at least 1 NIAD using pharmacy claims data. The interaction between past NIAD adherence and intention was tested. The sample included 340 people. There was an interaction between past NIAD adherence and intention to adhere to the NIAD ( P = 0.032). Intention did not predict future NIAD adherence in the past adherers and nonadherers groups, but its association measure was high among past nonadherers ( β = 5.686, 95% confidence interval [CI] −10.174, 21.546). In contrast, intention was mainly predicted by perceived behavioral control both in the past adherers ( β = 0.900, 95% CI 0.796, 1.004) and nonadherers groups ( β = 0.760, 95% CI 0.555, 0.966). The present study suggests that TPB is a good tool to predict intention to adhere and future NIAD adherence. However, there was a gap between intention to adhere and actual adherence to the NIAD, which is partly explained by the past adherence level in adults with type 2 diabetes.